Scrolling vs Studying: Dampak Cyberloafing terhadap Student Engagement Mahasiswa dalam Perkuliahan Daring - Fathimah Az Zahra; Indriyani Santoso (YASIN, 2026)
The phenomenon of cyberloafing in online lectures has become an issue that can affect students’ academic engagement, particularly in the context of digital learning. Although this issue has received attention in educational studies and academic psychology, research that specifically examines the relationship between cyberloafing and student engagement among students who actively participate in online lectures still needs to be strengthened. This study aims to analyze the relationship between cyberloafing and student engagement among students undergoing online lectures. This study used a quantitative approach with a correlational design, involving 84 students selected through purposive sampling. Data were collected using a cyberloafing scale and a student engagement scale, and were then analyzed using Pearson Product-Moment correlation. The results showed that the level of cyberloafing was in the low-to-moderate category, with a mean score of M = 53.01 from a theoretical range of 20–100, whereas student engagement was in the moderate-to-high category, with a mean score of M = 76.52 from a theoretical range of 24–120. The correlation analysis results indicated a significant negative relationship between cyberloafing and student engagement, with r = -0.422 and p = 0.000. These findings indicate that the higher students’ involvement in non-academic activities during online lectures, such as accessing social media or playing games, the lower their engagement in learning. The conclusion of this study emphasizes the importance of controlling cyberloafing to maintain students’ academic engagement. The implications of this study suggest that lecturers and educational institutions should design more interactive online learning and encourage students’ self-regulation so that learning engagement can be maintained.